Risk of venous thromboembolism in Asian patients with inflammatory bowel disease: a nationwide cohort study - Chan Mi Heo (Nature Portfolio, 2021)
Abstract Routine prophylaxis for venous thromboembolism (VTE) in Asian IBD patients has been controversial. We aimed to estimate the risk of VTE of Asian patients at different phases of IBD by incorporating patient-specific risk factors. In this cohort study, we analyzed the National Health Insurance claims data between 2012 and 2016 for the entire Korean population. We calculated incidence rates and hazard ratios for VTE. The overall VTE risk was higher in patients with IBD [adjusted hazard ratio (aHR), 2.06; 95% confidence interval (CI), 1.66–2.55], than in controls. When we compare the risk of VTE by different disease phases, the risk of VTE was the highest during post-operation period after IBD-related bowel surgery (aHR, 39.7; 95% CI 9.87–159.3), followed by during hospitalized periods with flare (aHR, 27.2; 95% CI 14.9–49.65) and during hospitalized periods with non-flare (aHR, 16.23; 95% CI 10.71–24.58). The incidence rate (per 1000 person-years) was 15.26 during hospitalized periods with a flare and 9.83 during hospitalized periods with non-flare. According to age groups, the incidence rate (per 1000 person-years) during hospitalized periods with flare was 14.53 in young patients (20–39 years) and 34.58 in older patients (60–80 years). During hospitalized periods with non-flare, the incidence rate was 3.55 in young patients and 23.61 in older patients. The prophylaxis of VTE for Asian patients with IBD should be recommended in older patients admitted to hospital and be considered in young patients who are hospitalized with a flare.